2012
DOI: 10.1111/j.1365-3059.2012.02607.x
|View full text |Cite
|
Sign up to set email alerts
|

Identity and variability of Pythium species associated with yield decline in aerobic rice cultivation in the Philippines

Abstract: The cultivation of aerobic rice in the tropics enables farmers to save water without lowering productivity. Unfortunately, this system suffers from declining yields due to a disease complex involving nematodes, pathogenic Pythium spp. and nutrient deficiencies. Assessing the impact of each underlying factor can contribute to efficient disease control measures. This study therefore investigated pathogenic and genotypic variability among Pythium species from affected aerobic rice fields in the Philippines using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Pythium DNA was quantified using the method described by Van Buyten et al . (), and plant DNA was quantified using a rice housekeeping gene (LOC_Os07g02340). The data indicated that P. graminicola massively infects the whole root system in wild‐type and empty vector lines, where P. graminicola DNA quantities represent 97% and 98%, respectively, of the total DNA extract at 7 dpi.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Pythium DNA was quantified using the method described by Van Buyten et al . (), and plant DNA was quantified using a rice housekeeping gene (LOC_Os07g02340). The data indicated that P. graminicola massively infects the whole root system in wild‐type and empty vector lines, where P. graminicola DNA quantities represent 97% and 98%, respectively, of the total DNA extract at 7 dpi.…”
Section: Resultsmentioning
confidence: 97%
“…These declining yields are associated with nutrient deficiencies (Kreye et al ., ; Nie et al ., ), as well as biotic factors, in which root‐affecting Pythium spp. ( Pythium graminicola and Pythium arrhenomanes ) and root‐knot nematodes (RKNs), such as Meloidogyne graminicola , are the predominant species (Bridge et al ., ; Dangal et al ., ; De Waele and Elsen, ; Soriano et al ., ; Tandingan et al ., ; Van Buyten et al ., ). In the case of RKNs, infective second‐stage juveniles (J2) penetrate the roots and migrate intercellularly towards the root apex, where they make a U‐turn and move upwards in the vascular bundles to the differentiation zone, where they settle and initiate permanent feeding sites called giant cells.…”
Section: Introductionmentioning
confidence: 97%
“…Pythium graminicola strain PB912 132, isolated from a diseased aerobic rice field in Los Bañ os, The Philippines (Van Buyten et al, 2012), was cultivated at 28°C on potato dextrose agar (PDA; Difco Laboratories). Rice seeds were surface sterilized by agitation in 2% sodium hypochlorite for 20 min, rinsed three times with sterile demineralized water, plated in square petri dishes (12 3 12 cm) on standard strength Gamborg B5/1% plant agar medium, and subsequently grown in a growth chamber at 28°C (day)/26°C (night) under 12-h photoperiod.…”
Section: Pythium Graminicola Bioassaysmentioning
confidence: 99%
“…Unlike most other experimentally tractable model plants, rice is a staple food for more than half the world and a model for monocots, which include cereal crops and biofuel grasses (Jung et al, 2008). P. graminicola, on the other hand, has recently been earmarked as one of the driving factors behind the progressive yield decline frequently observed in aerobic rice fields (Van Buyten et al, 2012). In contrast to the prevailing view that BRs boost plant innate immunity, our results provide compelling evidence that P. graminicola exploits endogenous BRs as virulence factors and hijacks the host BR machinery to inflict disease.…”
mentioning
confidence: 99%
“…These isolates exhibited different levels of virulence under in vitro conditions [3]. Isolates were cultured on 22 ml of potato dextrose agar (PDA; Difco Laboratories) at 28°C in the dark.…”
Section: Methodsmentioning
confidence: 99%